Media Pemberitaan Injil Melalui Tiktok Era 5.0 Perspektif Guichun di Jemaat Rantetallang - Garry Rulian (Program Studi Misiologi dan Komunikasi Kristen, 2023)
This article discusses the use of the TikTok application as a medium for preaching the Gospel in the 5.0 era, with a focus on Guichun Jun's perspective. This research was conducted at the Rantetallang congregation with the aim of explaining how TikTok can be an effective tool in spreading religious messages to the congregation and the wider community. In the ever-growing digital era, social media has become a powerful platform for conveying information and influencing culture. TikTok, as a very popular social media application, offers various interesting features that allow users to create and share short videos with creative effects. In this context, it is important to understand the potential of TikTok as a tool that can be used in religious contexts. The perspective of Guichun Jun, a prominent theologian, is used as a theoretical framework in this research. Jun proposed that in the 5.0 era, where technology is increasingly integrated with everyday life, churches and religious communities need to utilize social media as a tool to expand the reach of preaching the Gospel. This study involved in-depth analysis of theological texts written by Guichun Jun, as well as field research in the Rantetallang congregation. Through interviews with congregation members and TikTok users, researchers collected data about their perceptions of using TikTok as a medium for preaching the Gospel. This research also identified several challenges that must be faced, such as content that is not in accordance with religious values and the risk of losing the deep meaning in religious messages in short video format.